(untitled) (The Research of Medical Science Review, 2025)
Objective: To compute up to what extend the FNAC results are precise by correlating it with final histology. Study: retrospective review Methods: 132 patients, who presented with parotid swelling from the year 2014- 2023 were included in the study. Only patients under-went FNAC from Liaquat national hospital were included. Patient’s age, gender, diseases pattern and pathological characteristics were extracted from record. The FNAC and histology results were cross-tabulated in a 2 x 2 contingency table, from which we calculated the diagnostic accuracy, sensitivity, specificity, and positive and negative predictive values. Results: Out of 132 patients, mean age was 46.2 years with range of 12 to 80 years. 72 patients were males and 60 were females. The diagnosis on FNAC was correlated with histopathology. Statistical analysis showed FNAC had a sensitivity of 70%, specificity of 99%, positive predictive value of 93%, and negative predictive value of 94.8%. However, the overall accuracy in this study was determined to be 94.6%. The most common diagnosis was Pleomorphic adenoma (80 patients, 60.6%), Warthin tumors (27 patients, 20.5%), most common malignant tumor was Mucoepidermoid carcinoma (11 patients, 8.3%), followed by Adenocarcinoma (6 patients, 4.5 %). Some rare tumors are also found on final histology report included Dermatofibrosarcoma putuberance (1 patient, 0.8%) and Markel cell carcinoma (1 patients, 0.8%). Conclusions: This study found that FNAC correlated with histopathology in the diagnosis of parotid tumors. FNAC is useful in the preoperative assessment of parotid tumors as it provides a preoperative diagnosis.